2023
DOI: 10.1021/acs.nanolett.3c03089
|View full text |Cite
|
Sign up to set email alerts
|

Phase Interrogation Sensor Based on All-Dielectric BIC Metasurface

Zhenchao Liu,
Tingbiao Guo,
Qin Tan
et al.

Abstract: The low performance of sensors based on an all-dielectric metasurface limits their application compared to metallic counterparts. Here, for the first time, an all-dielectric BIC (bound states in the continuum) metasurface is employed for highly sensitive phase interrogation refractive index sensing. The proposed sensor is well analyzed, fabricated, and characterized. Experimentally, a high-performance BIC-based microfluidic sensing chip with a Q factor of 1200 is achieved by introducing symmetry breaking. A re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…It is compatible with semiconductor micronanofabrication processes (lithography, etching, etc.) [48,49].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is compatible with semiconductor micronanofabrication processes (lithography, etching, etc.) [48,49].…”
Section: Resultsmentioning
confidence: 99%
“…It is compatible with semiconductor micronanofabrication processes (lithography, etching, etc.) [48,49]. First, photoresist is spin-coated on a sufficiently cleaned quartz substrate, and after the photoresist is sufficiently cured, the PMMA nanoarray structure is obtained by electron beam lithography.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it is also found that increasing height of the nanorods leads to an enhanced sensing performance, which is due to the enlarged contacting surface area between the nanostructures to the environmental media. Liu et al propose and fabricate a similar metasurface array consisting of periodic silicon nanorod pairs placed on a silica substrate (figures 11(f) and (g)) [106]. With combined microfluidic chips, NaCl solutions with different mass fractions (0.00%, 0.10%, 0.30%, 0.50%, 0.70%, 1.00%, and 3.00%) are prepared to evaluate the sensing performance with RIs change from 1.318 to 1.358 (figure 11(h)).…”
Section: All-dielectric Infrared and Visible Metasurfacesmentioning
confidence: 99%
“…Different designs have been applied to enhance the coupling of the incoming light to the SPR [4,5]. The mechanisms of such devices are purely optical-, phase-, spectral-, angular-, or intensity-interrogated [6][7][8][9][10][11]. A modern simplification of these sensors is obtained by attaching them to photodetectors, which extract the measurable quantity from an electrical signal [12,13].…”
Section: Introductionmentioning
confidence: 99%